Microsponge: A Novel Approach for Topical Drug Delivery of Anti Rheumatoid Drugs - Joshi, Krupa (Asian Journal of Pharmaceutics (AJP), 2024)
Microsponge is one of the developing fields of science innovation, which can be capable of both regulated drug delivery and site-specific administration of drugs. The determination of the particular pharmaceutical formulations and way of distribution for delivery of the medicament is strongly influenced by the physical and chemical characteristics of the microsponge, such as the size of particles, distribution of particle size, transparency, and surface structure. An innovative technique for topical medicine delivery has also emerged: The microsponge. The topical methods further benefit from flexible formulations, more patient participation, increased safety and overall performance, and attractive characteristics. Immunomodulatory rheumatoid arthritis requires long-term therapy to control the condition. Long-term administration of the marketed oral dosage forms may result in liver damage. The topical way may represent a good alternative method for medication delivery with better drug stability, less adverse effects, and less frequent administration. Microsponges have the ability to entrap significant amounts of dosage and may also alter medication release due to its porous and spongy nature.